2018
DOI: 10.1080/19390211.2018.1454568
|View full text |Cite
|
Sign up to set email alerts
|

Oral Supplementation with Beta-Hydroxy-Beta-Methylbutyrate, Arginine, and Glutamine Improves Lean Body Mass in Healthy Older Adults

Abstract: Oral intake of beta-hydroxy-beta-methylbutyrate (HMB), arginine, and glutamine may ameliorate muscle loss by stimulating protein synthesis and decreasing protein degradation while simultaneously decreasing inflammation. Previous studies provide evidence for improvement in body composition with dietary supplementation of these ingredients among patients with muscle-wasting diseases. The objectives of this study were to examine the effects of this amino acid mixture on lean body mass, muscle volume, and physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 66 publications
0
53
0
Order By: Relevance
“…A recent study also showed the positive effect of HMB combined with arginine and glutamine on muscle mass. 72 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed the positive effect of HMB combined with arginine and glutamine on muscle mass. 72 …”
Section: Discussionmentioning
confidence: 99%
“…In community-dwelling older adults, we found that protein supplementation (25 to 46 g/day) was effective on muscle mass, strength, and physical performance in frail and sarcopenic subjects [27,28]. However, the effects of oral nutritional supplementation were limited in healthy subjects [24][25][26]. Three factors could explain these results: the participants had high protein intake at inclusion, the results may have been confounded by physical activity which was not reported or assessed, and most studies were underpowered (small sample size).…”
Section: Discussionmentioning
confidence: 95%
“…In healthy older adults, the effects of nutritional intervention on muscle mass, muscle strength, and physical performance were divergent. In a small sample, Ellis et al showed that a 6-month amino acid supplementation with beta-hydroxy-beta-methylbutyrate (HMB) improved lean body mass (52.9 ± 11.9 vs. 48.4 ± 11.4 kg, p = 0.036) and 12-step timed stair climb (4.86 ± 1.66 vs. 4.61 ± 0.80 s, p = 0.016) [24]. Zhu et al tested the effect of whey protein supplementation (30 g/day) during two years, in Australian subjects with baseline protein intake above 0.75 g/kg/day [25].…”
Section: Unimodal Nutritional Interventionsmentioning
confidence: 99%
“…however, adding L-glutamine to the mixture (3 g HMB, 14 g L-arginine, 14 g L-glutamine) administered for six months to healthy elderly increased their lean muscle mass (29). An important finding is a fact that between the SUP and PL groups, no statistically significant differences in the level of muscle cell damage markers, i.e.…”
Section: Discussionmentioning
confidence: 96%